Free Cyanide Induced Physiological Changes in the Freshwater Fish, Poecilia Reticulata - Mahesh Anand Goudar3, M.S. Prashanth1*, H.A. Sayeswara2 and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Static renewal bioassay test were conducted to determine the toxicity of free cyanide (sodium cyanide) to the freshwater fish, Poecilia reticulate. The fish were exposed to different concentrations of sodium cyanide and rate of mortality was recorded for 96 hr. The LC50 value of sodium cyanide for 96 hr was found out to be 9.13 Ã‚Âµg/L. Behavioural changes were observed when fish exposed to sodium cyanide showed increased opercular movement, increased surface behaviour, loss of equilibrium, increased secretion of mucus, irregular swimming activity and aggressiveness. The swimming behaviour was in a cork-screw pattern, rotating along horizontal axis was more prominent in lethal concentration. In sub lethal treatment, the schooling behaviour of the fish was slowly disrupted, and the ventilation rate increased. The fish at 15th day of exposure exhibited balanced swimming and active feeding and behaved in normal way. Decreased level of oxygen consumption was recorded in lethal concentration for 1st to 4th day (-36.12 to -70.93%), but in sub lethal concentration, it was improved and reached normal level at 15th day (-16.40 to -7.16%). The decrement may be due to the respiratory distress as a consequence of the impairment of oxidative metabolism.